Approved budget for 1992 : Osun State (Osun, Nigeria : Osun State of Nigeria, 1992)
This book contains an estimated budgetary allocation for Osun state ministries and agencies for the year 1992. It includes overheads, security volts and other financial burden of the state government.
asm 11/04/2019
Loans
Keywords: Budget; Nigeria